KREDIT-MODUL TIZIMI SHAROITIDA BO‘LAJAK GEOGRAFIYA O‘QITUVCHILARIGA MUSTAQIL TA’LIMNI SAMARALI TASHKIL ETISH VOSITALARI - Abdimurotov, O.U. (SCIENCE and SOCIETY, 2024)
The article analyzes the state of independent education in higher education institutions, modern means of its effective organization, that is, the possibilities of strengthening geographical knowledge and developing professional competence using information and communication technologies.